Is burnout solely job-related? A critical comment - Bianchi, Renzo; Truchot, Didier; Laurent, Eric; Brisson, Romain; Schonfeld, Irvin Sam (My University, 2014)
Within the field-dominating, multidimensional theory of burnout, burnout is viewed as a work-specific condition. As a consequence, the burnout syndrome cannot be investigated outside of the occupational domain. In the present paper, this restrictive view of burnout's scope is criticized and a rationale to decide between a work-specific and a generic approach to burnout is presented. First, the idea that a multidimensional conception of burnout implies a work-restricted scope is deconstructed. Second, it is shown that the burnout phenomenon cannot be confined to work because chronic, unresolvable stress - the putative cause of burnout - is not limited to work. In support of an integrative view of health, it is concluded that the field-dominating, multidimensional theory of burnout should abandon as groundless the idea that burnout is a specifically job-related phenomenon and define burnout as a multi-domain syndrome. The shift from a work-specific to a generic approach would allow both finer analysis and wider synthesis in research on chronic stress and burnout.
Keywords: Burnout; Maslach Burnout Inventory; chronic stress; generic approach; occupational stress; scope